RENAL INVOLVEMENT IN CHILDREN WITH CELIAC DISEASE - E. A. Trifonova; N. V. Rusakova (Вопросы современной педиатрии, 2012)
The literature review deals with renal involvement in children with celiac disease. The article contains common conceptions on possible variants of renal disorders and mechanisms of development of dysmetabolic and IgA-nephropathy in children with celiac disease.